Evaluation of cigarette flavoring quality via surface-enhanced Raman spectroscopy. Issue 77 (11th September 2018) - Xu, Shi-Qiang; Wen, Bao-Ying; Zhang, Li-Na; Zhang, Hua; Gao, Yang; Nataraju, Bodappa; Xu, Li-Ping; Wang, Xin; Li, Jian-Feng; Tian, Zhong-Qun
Abstract : Herein, surface-enhanced Raman spectroscopy (SERS) combined with principal component analysis (PCA) has been successfully applied in the evaluation of cigarette flavoring quality using monolayer films of Au nanoparticles as substrates. Abstract : Herein, surface-enhanced Raman spectroscopy (SERS) combined with principal component analysis (PCA) has been successfully applied in the evaluation of cigarette flavoring quality using monolayer films of Au nanoparticles as substrates. With such a method, even a slight difference in the formula of the essence that cannot be directly identified by SERS can be distinguished.